Time Perspective of Forced Migrants within the National Boundaries and Abroad - Plokhikh, Viktor; Popovych, Ihor; Shevchenko, Nataliia; Losiyevska, Olga; Kolly-Shamne, Anzhelika; Akimov, Rustem (Journal of Education Culture and Society, 2025)
Aim. The aim is identification of differences in organisation of time perspective in forced migrants within the national boundaries and beyond the country under martial law in relation to prolonged psychological stress and steady changes in mental states.Methods. There were 136 young and middle-aged research participants: 59 forced migrants in Ukraine (Group 1) and 77 forced migrants staying abroad (Group 2). The methods used: “Time Perspective Inventory” (Zimbardo & Boyd, 1999); the scale “Time Competence” from the test determining an individual’s self-actualisation (Shostrom, 1964); the Freiburg Personality Inventory (FPI, Form В) (Fahrenberg, Hampel & Selg, 2010).Results. The Mann-Whitney U-test allowed establishing the advantage of Group 2 over Group 1 by the parameters: “negative past” (U =1781.00; p =.031); “hedonistic present” (U=1620.00; p=.004); “fatalistic present” (U=1560.00; p=.002), and also the advantage of Group 1 over Group 2 by the parameters: “neuroticism” (U = 1715.50; p = .013); “sociability” (U = 1464.50; p